Databases in networked information systems 7th International Workshop, DNIS 2011, Aizu-Wakamatsu, Japan, December 12-14, 2011. Proceedings - DNIS 2011 University of Aizu) (2011; Kikuchi, Shinji; Madaan, Aastha; Sachdeva, Shelly; Bhalla, Subhash; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 7th International Workshop on Databases in Networked Information Systems, DNIS 2011, held in Aizu-Wakamatsu, Japan in December 2011. The 18 revised full papers presented together with 6 invited talks and 1 keynote lecture were carefully reviewed and selected for inclusion in the book. The workshop generally puts the main focus on data semantics and infrastructure for information management and interchange. The papers are organized in topical sections on cloud computing; access to information resources; information and knowledge management; bio-medical information management; information extraction from data resources; geo-spatial decision making; networked information systems: infrastructure.
Electronic reproduction.
Keywords: Databases -- Congresses; Computer networks -- Congresses; Electronic books